Selected peer-reviewed articles from the 2016 world international conference on sciences (WICS 2016), Kuala Lumpur, Malaysia, 5-7 december, 2016 - Basir N.; Aminuddin M.M.M.; Darsono A.M.B.; Misran M.H.; Sulaiman H.A.; Othman M.A. (American Scientific Publishers, 2024)
Indexed by SCOPUS